Case Report: Advanced colorectal cancer diagnosed and treated with chemotherapy during pregnancy - Galante, Arianna; Cerbone, Marco; Sorgente, Giuseppe; Moramarco, Pasquale; Difonzo, Tommaso; Cormio, Gennaro; Marinaccio, Marco; Alfonso, Raffaello; Cicinelli, Ettore; Vimercati, Antonella (Frontiers in Oncology, 2025)
IntroductionCancer during pregnancy is a rare event and often presents at an advanced stage due to delayed diagnosis. Clinical symptoms are frequently misattributed to normal pregnancy changes, leading to diagnostic challenges. Moreover, concerns regarding fetal safety limit the use of certain imaging modalities and treatment options. Managing cancer in pregnancy requires careful coordination across specialties to balance maternal treatment with fetal preservation.Case-reportWe present the case of a pregnant woman diagnosed in the second trimester with advanced metastatic colorectal cancer. The disease involved multiple intra-abdominal sites, and the patient was managed through a multidisciplinary approach. Chemotherapy with FOLFOX scheme was administered during the second and third trimester of pregnancy, leading to a favorable clinical and radiologic response. Delivery was planned at term, with no complications for the newborn. Postpartum oncologic management was continued without delay.ConclusionThis case highlights the importance of individualized care in such complex scenarios and the feasibility and safety of administering chemotherapy during pregnancy.